Silencing circular RNA circ_0054537 and upregulating microRNA-640 suppress malignant progression of renal cell carcinoma via regulating neuronal pentraxin-2 (NPTX2). Issue 1 (1st January 2021) - Pei, Long; Lv, Xianqiang; Jia, Gaopei; Tan, Xiaoliang; Li, Ming; Zhang, Aili
ABSTRACT: Hsa_circ_0054537 (circ_0054537) is a novel tumor-related circular RNA in renal cell carcinoma (RCC), and we intended to ascertain its dysregulation and functions in RCC malignant progression, as well as the underlying mechanism via serving as competing endogenous RNA (ceRNA). In this research, using real-time quantitative PCR, we found circ_0054537 was upregulated in RCC tissues and cells, and distributed throughout the cytoplasm. Then, functional effects of circ_0054537 in RCC were detected using cell counting kit-8, transwell, flow cytometry and glycolysis stress test and adenosine Triphosphate (ATP) assays. The results uncovered that circ_0054537 knockdown inhibited cell proliferation, migration, invasion, autophagy and glycolysis, but promoted apoptosis in RCC cells. Notably, circ_0054537 was identified as a ceRNA for microRNA (miR)-640, and miR-640 could target neuronal pentraxin-2 (NPTX2), as evidenced by dual-luciferase reporter assay and RNA immunoprecipitation assay. Besides, miR-640 downregulation or NPTX2 overexpression partly overturned the tumor suppressor function of circ_0054537 silence and miR-640 overexpression in RCC cells. Additionally, RCC cell growth in vivo was retarded by circ_0054537 silence. In conclusion, circ_0054537/miR-640/NPTX2 ceRNA pathway regulated RCC malignant progression in vitro and curbed RCC tumor growth in vivo, which could be a potential diagnosis and therapeutic target of RCC.